2018
DOI: 10.1002/ejic.201800075
|View full text |Cite
|
Sign up to set email alerts
|

Zero Field SMM Behavior and Magnetic Refrigeration in Rare Heterometallic Double Stranded Helicates of Cu2Ln2 (Ln = Dy, Tb, Gd)

Abstract: The strategic design and synthesis of new double stranded helical structures, namely [Cu 2 Ln 2 (H 2 L 1 ) 2 (L 2 ) 2 (OMe)-(NO 3 )]·8MeOH (1: Ln = Dy III ), [Cu 2 Ln 2 (H 2 L 1 ) 2 (L 2 ) 2 (H 2 O)(OMe)-(NO 3 )]·xH 2 O·7MeOH (2: Ln = Tb III , x = 0.5; 3: Ln = Gd III , x = 1) and [Cu 2 Ln 2 (HL 1 ) 2 (L 2 ) 2 (MeOH) 2 ]·xMeOH (4: Ln = Dy III , x = 8.5; 5: Ln = Tb III , x = 8; 6: Ln = Gd III , x = 8.66), has been achieved by using a flexible helical ligand and a rigid tridentate ligand. Butanedihydrazide-bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…Such a strategy was successful in providing many Ni-4f and Cu-4f complexes of varying nuclearity . Phenol-based Schiff bases are well-known to provide heterometallic coordination clusters from one-pot reactions involving a mixture of 3d and 4f metal ion salts and ligands. , …”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy was successful in providing many Ni-4f and Cu-4f complexes of varying nuclearity . Phenol-based Schiff bases are well-known to provide heterometallic coordination clusters from one-pot reactions involving a mixture of 3d and 4f metal ion salts and ligands. , …”
Section: Introductionmentioning
confidence: 99%
“…Generally, Cu‐lanthanide units (especially Cu−Gd) in polynuclear complexes are found to exhibit ferromagnetic interaction among them [1a–d,f–h,20] . Several schematic pathways have already been proposed to explain the origin of the interaction between the magnetic centres in such complexes [1c,6a,8a,11a,16b,d,20–21] . BS‐DFT calculation shows the presence of both ferromagnetic and antiferromagnetic exchange coupling between Cu II and Ln III centres in the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…With the simultaneous addition of Cu 2+ and Ln III ions, 3d−4f heterometallic double strand helicates M31-Dy and M32-Dy were prepared (Figure 50). 326 The coordination environment of the metal centers exerted changes in their magnetic properties. Magnetic susceptibility measurements (ac field) suggested that these heterometallic helicates demonstrated slow magnetic relaxation and magnetic refrigeration behaviors.…”
Section: Magnetismmentioning
confidence: 99%